Next‐generation Gene Silencers for Cancer Immunotherapy - Ng, Aik Seng (2017)
In the tumor microenvironment, immune evasion entails a reciprocal interaction between cancer cells and T-cells. This leads to the inhibition of the tumor killing ability of T-cells via immune checkpoint protein interactions, mainly - PD-1/PD-L1 & CTLA-4/B7. [2nd Award]